1998
DOI: 10.1002/hep.510280629
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in hepatitis B DNA polymerase associated with resistance to lamivudine do not confer resistance to adefovirin vitro

Abstract: To determine whether adefovir is active against lamivudine-resistant hepatitis B virus (HBV), the inhibition constants of adefovir diphosphate and lamivudine triphosphate for wild-type and mutant human HBV DNA polymerases, which contain amino acid substitutions associated with lamivudine resistance, were compared. Recombinant wildtype and mutant human HBV DNA polymerases were expressed and substantially purified using a baculovirus expression system and immunoaffinity chromatography. HBV DNA polymerase mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
176
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(189 citation statements)
references
References 31 publications
11
176
0
2
Order By: Relevance
“…We previously reported that the lamivudine-resistant mutations M552I, M552V, L528MϩM552I, and L528MϩM552V mutant HBV polymerases displayed resistance to LAMTP with K i values increased by 8-to 25-fold compared with that of wild-type HBV polymerase and that all these mutants remained sensitive to ADVDP. 30 In this study, we found that the M552I and L528MϩM552V mutants remained sensitive to PCVTP with K i values increased by 1.1-and 2.5-fold, respectively. However, the M552V mutant displayed moderately decreased sensitivity to PCVTP (3.1-fold) ( Table 2).…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…We previously reported that the lamivudine-resistant mutations M552I, M552V, L528MϩM552I, and L528MϩM552V mutant HBV polymerases displayed resistance to LAMTP with K i values increased by 8-to 25-fold compared with that of wild-type HBV polymerase and that all these mutants remained sensitive to ADVDP. 30 In this study, we found that the M552I and L528MϩM552V mutants remained sensitive to PCVTP with K i values increased by 1.1-and 2.5-fold, respectively. However, the M552V mutant displayed moderately decreased sensitivity to PCVTP (3.1-fold) ( Table 2).…”
Section: Resultsmentioning
confidence: 49%
“…The V521L and L528M mutations only displayed 3.1-fold decreased sensitivity compared with 8-to 25-fold increases in K i values for LAMTP for mutations associated with lamivudine resistance in the same assay. 30 However, the 3-fold decreased sensitivity could be enough to cause clinical resistance to famciclovir. 33 Because suppression of HBV replication by famciclovir in chronically infected patients appears to be suboptimal, famciclovir has a low threshold to become clinically ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Adefovir dipivoxil (ADV), an oral pro-drug of adefovir, has an antiviral activity against not only wild-type HBV but also LAM-resistant HBV mutants in vitro and in vivo. [10][11][12][13] Therefore, a switch to ADV is usually recommended for patients with LAM-resistant CHB. 14 In contrast to LAM, ADV therapy in treatment-naïve patients is associated with delayed and infrequent emergence of drug-resistant mutations.…”
mentioning
confidence: 99%